Plotting chart Atlantic sector of Antarctica / Publication of the Office of the Chief of Hydographic Service of the Navy (USSR) - United States. Hydrographic Office (Washington, DC : U.S. Navy Hydrographic Office, 1959)
1st ed., 1955. New Ed., 1958. Reproduced by the U.S. Navy Hydrographic Office (November 1959) from U.S.S.R. chart Map labels in Russian. Titles and publication information in Russian and English.; Includes sheet coverage key; "U.S.S.R. 338" -- margins Grayscale; 1:7,250,000